2017
DOI: 10.1016/j.celrep.2017.01.068
|View full text |Cite
|
Sign up to set email alerts
|

Rapid State-Dependent Alteration in Kv3 Channel Availability Drives Flexible Synaptic Signaling Dependent on Somatic Subthreshold Depolarization

Abstract: Summary In many neurons, subthreshold depolarization in the soma can transiently increase action potential (AP)-evoked neurotransmission via analog-to-digital facilitation. The mechanisms underlying this form of short-term synaptic plasticity are unclear, in part, due to the relative inaccessibility of the axon to direct physiological interrogation. Using voltage imaging and patch-clamp recording from presynaptic boutons of cerebellar stellate interneurons, we observed that depolarizing somatic potentials read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 64 publications
1
44
2
Order By: Relevance
“…Several reports have suggested that Kv3.3 or Kv3.4 subunits could be differentially incorporated into somatic versus presynaptic channels in the cerebellum and spinal cord (Brooke et al . 2004; 2010; Rowan & Christie, 2017). But the extent to which all Kv3 subunits contribute to presynaptic AP repolarization and thus influence transmitter release is an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that Kv3.3 or Kv3.4 subunits could be differentially incorporated into somatic versus presynaptic channels in the cerebellum and spinal cord (Brooke et al . 2004; 2010; Rowan & Christie, 2017). But the extent to which all Kv3 subunits contribute to presynaptic AP repolarization and thus influence transmitter release is an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, another gene involved in myelin maintenance, Mal2, is upregulated more than twofold. Two CNS-related DEGs were Kcnc4, a voltage-gated potassium ion channel 48 , and Gda, a guanine deaminase concentrated in the brain that regulates microtubule assembly 49 . Kcnc4 conducts potassium outward following an action potential, restoring the membrane to resting state 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Two CNS-related DEGs were Kcnc4, a voltage-gated potassium ion channel 48 , and Gda, a guanine deaminase concentrated in the brain that regulates microtubule assembly 49 . Kcnc4 conducts potassium outward following an action potential, restoring the membrane to resting state 48 . Likewise, the increase in Gda expression could indicate a misregulation of the cytoskeleton or an increase in cellular outgrowths.…”
Section: Discussionmentioning
confidence: 99%
“…This analog-digital facilitation induced by depolarization (d-ADF) is not exclusively observed in glutamate-releasing neurons but it is also seen on GABA-releasing interneurons. In this case, the mechanism depends either on spike-waveform through presynaptic Kv3.4 [29 ] or on the increase in basal calcium during subthreshold depolarization via activation of P/Q type calcium channels [30,31]. Modulation of basal calcium concentration by presynaptic membrane potential is also the main mechanism of d-ADF in auditory neurons [32,33], mitral cells of the olfactory bulb [34] and sensory neurons of the Aplysia [35].…”
Section: Analog-digital Signaling In the Axonmentioning
confidence: 99%